Quantitative dam break analysis on a reservoir earth dam - Kho, F. W. L.; Law, P.L; Lai, S.H.; Oon, Y.W.; Ngu, L.H; Ting, H. S. (Springer Science, 2009)
Mathematical simulations on dam break or failure using BOSS DAMBRK hydrodynamic flood routing dam break model were carried out to determine the extent of flooding downstream, flood travel times, flood water velocities and impacts on downstream affected residences, properties and environmental sensitive areas due to floodwaters released by failure of the dam structure. Computer simulations for one of the worse-case scenarios on dam failure using BOSS DAMBRK software accounted for dam failure, storage effects, floodplains, over bank flow and flood wave attenuation. The simulated results reviewed a maximum flow velocity of 2.40 m/s with a discharge of approximately 242 m³/s occurred at 1.00 km downstream. The maximum discharge increased from 244 m3/s (flow velocity = 1.74 m/s occurred at 8th. km) to 263 m3/s (flow velocity = 1.37 m/s occurred at 12th. km); about a 39% drop in flow velocity over a distance of 4.00 km downstream. If the entire dam gives way instantly, some spots stretching from 0.00 km (at dam site) to approximately 3.40 km downstream of the dam may be categorized as “danger zone”, while downstream hazard and economic loss beyond 3.40 km downstream can be classified as “low” or “minimal” zones.